Gully erosion on alluvial fans can be mitigated by altering the hydrological connectivity between an alluvial fan and the contributing catchment: a study in the Lhasa River basin. (17th April 2022) - Li, Jianjun; Zhao, Chunjing; Chen, Tongde; Jiao, Juying; Wang, Haolin; Lin, Hong; Wang, Nan; Chen, Yixian; Cao, Xue; Xu, Qian
Abstract: In the Lower Lhasa River basin of the Tibetan Plateau, gully erosion poses a threat to alluvial fans (AF), which are the main available land resource for agriculture. Runoff from the whole contributing catchment is concentrated in AF, which makes influencing factors of AF gully erosion more complex than it is for hillslopes. There is a lack of quantitative research about the influencing factors and mechanisms of AF gully erosion. The main objectives of this study were to: (1) quantify gully erosion on AF; and (2) identify the controlling factors of gully erosion on AF. The gullies of 12 AF were investigated by unmanned aerial vehicle (UAV). To help understand better the gully erosion on AF, nine morphological parameters were measured, four gully quantitative characteristics were calculated, and 16 factors affecting the gully erosion on AF were analyzed. The gully width–depth ratio of over 20 on the studied AF is larger than that usually seen in other regions. The mean value of gully amount density (GAD), gully density (GD), the degree of gully dissection (GDD), and gully volume modulus (GVM) were 26.51 km − 2, 4.93 km·km − 2, 7.16%, and 1.28 × 10 −4 km 3 ·km − 2, respectively. Linear correlations showed a significant ( p < 0.05) relationship between the gully quantitative characteristics of AF and the catchment gully density. So, catchment gully density may indirectly affect gully erosion on AF by influencing hydrological connectivity and then changing generation and confluence processes of runoff in catchment. Therefore, gully erosion on AF can be mitigated by shifting hydrology pathway on AF and reducing hydrological connectivity in contributing catchment.